Estudo fitoquímico e bioatividade de espécies de Meliaceae sobre Spodoptera frugiperda e análises espectroscópicas do inseto sob a ação da cedrelona - Freitas, Samya Danielle Lima de (2014)
Spodoptera frugiperda is a major pest of maize and its damage may lead to reduction of agricultural production. The use of synthetic insecticides has been the primary method of pest control, but their indiscriminate use has has altered the selection of populations, as well as damage to human health and environment.Thus, the study of insecticidal plants as a promising tool to control of pest insects have been stimulated. Good results were obtained previously with extracts of T. pallida, T. pallens and To. ciliata on larvae of S. frugiperda, but there are no studies related to metabolization by the insect of natural substances derived from these species. Therefore the goals of this study were to isolate and identify secondary metabolites of T. pallida, T. pallens and To. ciliata to assay them, and to understand how these compounds are metabolized by caterpillars at different larval stages. The phytochemical study provided isolation and identification of steroids sitosterol, stigmasterol and campesterol, triterpenes dammaradienol and 30-normetilenocicloartan- 3β-ol, limonoids cedrelone and 23-hidrooxicedrelone, coumarins siderin, scopoletin and 4-methoxy-5- methylcoumarin, flavonoids catechin, epicatechin and gallocatechin, indole-3-carbaldehyde, protocatechuic acid, inosil 5'- nucleoside and a purine adenine. Insecticides tests of ingestion against S. frugiperda were performed with crude extracts, fractions and pure substances. The best results were obtained from two species of Trichilia, where the branches fraction of T. pallens led to 100% larval mortality. Chemical studies of the metabolism of the insect was developed with the limonoid cedrelone, which was highly active. Thus, in order to understand how insects metabolize this active principle, some strategies were used to detect cedrelone in S. frugiperda larvae feeded with artificial diet containing this limonoid. The study of 1st instar larvae by Nuclear Magnetic Resonance (600 MHz) identified cedrelone intact in these extracts. The analysis of the extracts of the faeces of the fifth instar S. frugiperda feeded at 5 and 24 hours with diet enriched in cedrelone by Mass Spectrometry (LTQ-Orbitrap Velos), demonstrated that the metabolization pathway of cedrelone takes a longer time to be activated, because in 5 hours the limonoid was almost totally excreted intact in the faeces. In 24 hours, the insect metabolized a high amount of cedrelone, the metabolic products were released in faeces and a small amount of intact cedrelone, observing values below 500 ng when it was quantified. In metabolic activity assays of the insect, we observed an increase in relative metabolic rate and metabolic cost after ingestion of the active ingredient, which may be related to the attempted detoxification of the compound by the insect. The study of the microbiota associated with S. frugiperda by MALDITOF/ MS enabled the secure identification of micro-organisms isolated from treatments cedrelone and control at genus Enterococcus, and the specie E. mundtii was identified for all treatments. These micro-organisms seems to be associated with metabolism of cedrelone by the insect. Furthermore in this work it were carried out tests of inhibition of acetylcholinesterase enzyme in screening mode searching for potential candidates for natural insecticides, with the best results observed for cedrelone.